Experimental application-driven architecture analysis of an SIMD/MIMD parallel processing system - Bronson, E.C.; Casavant, T.L.; Jamieson, L.H. (IEEE transactions on parallel and distributed systems, 1990)
An experimental analysis of the architecture of an SIMD/MIMD parallel processing system is presented. Detailed implementations of parallel fast Fourier transform (FFT) programs were used to examine the performance of the prototype of the PASM (Partitionable SIMD/MIMD) parallel processing system. Detailed execution-time measurements using specialized timing hardware were made for the complete FFT and for components of SIMD, MIMD, and barrier-synchronized MIMD implementations. The component measurements isolated the effects of floating-point arithmetic operations, interconnection network transfer operations, and program control overhead. The measurements allow an accurate extrapolation of the execution time, speedup, and efficiency of the MIMD, SIMD, and barrier-synchronized MIMD programs to a full 1024-processor PASM system. This constitutes one of the first results of this kind, in which controlled experiments on fixed hardware were used to make comparisons of these fundamental modes of computing. Overall, the experimental results demonstrate the value of mixed-mode SIMD/MIMD computing and its suitability for computational intensive algorithms such as the FET.< >